Information Disclosure and the Multinational Corporation (Book). - Hendrickson, Harvey S.; Lee, Thomas A. (The Accounting Review, 1985)
Abstract Reviews the book "Information Disclosure and the Multinational Corporation," by S.J. Gray, L.B. McSweeney and J.C. Shaw.